Transient effects in droplet ignition phenomenon - Fachini, Fernando F.; Liñán, Amable M. (Combustion and flame, 1997)
We discuss the transient effects of mass and energy accumulation processes and of an applied acoustic field interaction on the droplet ignition phenomenon. In order to observe simultaneously the influence of those processes on the ignition, we assume that the chemical reaction occurs in the droplet unsteady far field, where the transient accumulation processes and the acoustic field are as important as the other processes (i.e., the conduction process and the chemical reaction). We also consider the Lewis number as being constant and nonunity. The results show that the ignition time is modified by the acoustic field.